2016
DOI: 10.1097/mnm.0000000000000523
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic assessment of Merkel cell carcinoma

Abstract: F-FDG PET-CT altered the stage of one of four patients and changed the management of one of seven MCC patients. In the majority of patients, a negative F-FDG PET-CT study excluded active MCC with a high degree of confidence. PET-CT contributed toward patient management when performed for staging and restaging, monitoring response to treatment, and suspected recurrent disease, but not in the routine follow-up of asymptomatic patients with MCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 17 publications
1
18
0
6
Order By: Relevance
“…Diagnostic tests shall include those employed in the diagnosis of melanoma. While current data calls for using 18 F‐FDG PET/CT as primary modality , it is important to ascertain in advance whether this procedure will be covered by health insurance funds in an outpatient setting. Should this imaging technique not be available, the initial diagnostic workup shall include CT of the thorax and abdomen as well as cranial MRI .…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnostic tests shall include those employed in the diagnosis of melanoma. While current data calls for using 18 F‐FDG PET/CT as primary modality , it is important to ascertain in advance whether this procedure will be covered by health insurance funds in an outpatient setting. Should this imaging technique not be available, the initial diagnostic workup shall include CT of the thorax and abdomen as well as cranial MRI .…”
Section: Diagnosismentioning
confidence: 99%
“…Zur Ausbreitungsdiagnostik sollen in Analogie zum malignen Melanom Schnittbildverfahren eingesetzt werden. Die aktuelle Datenlage spricht für den primären Einsatz der 18 F-FDG-PET/CT [8,[50][51][52][53][54][55][56], allerdings sollte die Kostenübernahme im ambulanten Bereich vorab geklärt werden. Sofern dies nicht zur Verfügung steht, soll die initiale Ausbreitungsdiagnostik ein CT-Thorax/Abdomen und MRT-Schädel beinhalten [57].…”
Section: Ausbreitungsdiagnostik Bei Erstdiagnoseunclassified
“…Given the aggressive biological nature of MCC and the patient demographic, careful pre‐treatment staging is appropriate. It has been suggested that Fluorine‐18 Fluorodeoxyglucose (FDG) Positron Emission Tomography/CT (PET) imaging prior to treatment may upstage 25–33% of patients and alter the management in 14–43% of patients . A systematic review and meta‐analysis of PET by Treglia et al .…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that Fluorine-18 Fluorodeoxyglucose (FDG) Positron Emission Tomography/CT (PET) imaging prior to treatment may upstage 25-33% of patients and alter the management in 14-43% of patients. 5,6 A systematic review and meta-analysis of PET by Treglia et al 7 demonstrated high sensitivity (90%) and specificity (98%) in a quantitative analysis of six studies involving 92 patients.…”
Section: Introductionmentioning
confidence: 99%
“…Zur Ausbreitungsdiagnostik sollen in Analogie zum malignen Melanom Schnittbildverfahren eingesetzt werden. Die aktuelle Datenlage spricht für den primären Einsatz der 18 F‐FDG‐PET/CT , allerdings sollte die Kostenübernahme im ambulanten Bereich vorab geklärt werden. Sofern dies nicht zur Verfügung steht, soll die initiale Ausbreitungsdiagnostik ein CT‐Thorax/Abdomen und MRT‐Schädel beinhalten .…”
Section: Diagnostikunclassified